Internal Control Analysis of Asset Management System at Hospital of Tanjungpura University - Nor, Sahar Rutin; Indah, Djunita Permata; Heniwati, Elok (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This research aims to analyze internal control in the asset management system at Hospital of Tanjungpura University. With a focus on environmental control, risk assessment, activity control, information and communication as well as monitoring in hospitals. This research method involves direct interviews with hospital staff to understand existing internal control practices. The results of this research show that the hospital has implemented environmental control well, but is still hampered by the manual recording system on medical devices. Monitoring of the management of medical devices has been carried out well through monthly cross checks and periodic evaluations. The recommendations given aim to increase efficiency by implementing a computerized asset recording system, strengthening internal controls related to inventory procurement documents, and improving communication between employees. With these improvement steps, it is hoped that hospitals can improve the quality of service and effectiveness of medical equipment management.